The effect of sports on physical development - Kamoliddin Hukimayev (Genius Journals, 2023)
In this article, the impact of sports on physical development, the main advantages of playing sports, the most important factors of sports physical development, and specific responsibilities of sports in increasing physical development are discussed.
Keywords: sports; physical development; regular sports